Challenging Gender Binaries in A ‘Journey to Honor’: A Feminist Critique of Performativity in Mulan (2020) Movie - Kusen, Felicia Jessica; Noah, Abimanyu; Setiawan, Steven Febryan; Silaen, Gwyneth Lillian (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This study examines the portrayal of gender roles of the characters and the social expectations in ‘Mulan,’ (2020) the live-action movie, using the feminist theory of gender performativity by Butler, J. (1990). The research focuses on how Mulan’s character challenges traditional gender roles in Chinese society, the significance of